2019
DOI: 10.1002/smj.3079
|View full text |Cite
|
Sign up to set email alerts
|

Principles or templates? The antecedents and performance effects of cross‐border knowledge transfer

Abstract: Research Summary Strategic use of codified knowledge across borders can be a vital component for project‐based work. Analyzing 237 global consulting projects, we examine the performance effects of drawing upon different types of codified knowledge. We argue and find that using principle‐based forms of knowledge is likely to improve a project's customer responsiveness, whereas using template‐based knowledge increases a project's cost effectiveness. We also explore what drives project managers to select differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 62 publications
(87 reference statements)
0
14
0
Order By: Relevance
“…A valuable knowledge-based resource that underlies organizational capabilities for knowledge creation and knowledge sharing in global environments is the international experience of managers and employees (Tasheva and Nielsen, 2020). Defined as exposure to or interactions with members or elements of a different culture (Maddux et al, 2021), international experience stimulates knowledge creation through innovative problem-solving (Bantel and Jackson, 1989), enhanced creativity (Maddux and Galinsky, 2009) and superior leveraging of organizational knowledge (Oldroyd et al, 2019). It facilitates knowledge sharing because internationally experienced individuals have better and more flexible communication skills (Backmann et al, 2020;Jang, 2017;Hong, 2010), exhibit increased levels of interpersonal trust (Chua et al, 2012;Cao et al, 2014), display reduced outgroup bias (Tadmor et al, 2018) and have greater tendency toward facilitating knowledge flow (Wang, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…A valuable knowledge-based resource that underlies organizational capabilities for knowledge creation and knowledge sharing in global environments is the international experience of managers and employees (Tasheva and Nielsen, 2020). Defined as exposure to or interactions with members or elements of a different culture (Maddux et al, 2021), international experience stimulates knowledge creation through innovative problem-solving (Bantel and Jackson, 1989), enhanced creativity (Maddux and Galinsky, 2009) and superior leveraging of organizational knowledge (Oldroyd et al, 2019). It facilitates knowledge sharing because internationally experienced individuals have better and more flexible communication skills (Backmann et al, 2020;Jang, 2017;Hong, 2010), exhibit increased levels of interpersonal trust (Chua et al, 2012;Cao et al, 2014), display reduced outgroup bias (Tadmor et al, 2018) and have greater tendency toward facilitating knowledge flow (Wang, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…As the data are updated only to 2018 and there is no essential change in the past year, the 2018 data are used as an alternative supplement to 2019. Informal institutions are measured by Hofstede’s national culture data (Kostova et al , 2020; Oldroyd et al , 2019), which include six dimensions: power distance, individualism versus collectivism, masculinity versus femininity, uncertainty avoidance, long-term versus short-term orientation and indulgence versus restraint. The missing data from a few countries are supplemented by data from countries (regions) adjacent to their geographical locations.…”
Section: Methodsmentioning
confidence: 99%
“…Second, cross-border M&As can promote technological innovation through two-way knowledge transfers and technology integration (Hansen et al , 2016; Li et al , 2019; Steigenberger, 2017). More specifically, based on the intention to acquire strategic assets, the parent company and the subsidiary actively carry out two-way knowledge transfers during post-merger integration (Cassiman and Valentini, 2016), thereby promoting the realization of dynamic knowledge coupling and collaborative innovation (Oldroyd et al , 2019; Sikimic et al , 2016). Among them, knowledge transfers from the host country to the parent company are conducted not only because the R&D (research and development) oriented subsidiary has advanced heterogeneous knowledge or technology but also because the subsidiary plays a “bridging” role in the knowledge transfers and technology spillovers between the host country and the parent company (Burmeister et al , 2018).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…“Cross-border” is not just a way of crossing and merging but also an open thinking pattern of an organization (Joshi et al , 2009). It is also commonly called as “boundary-crossing” or “boundary-spanning” (Oldroyd et al , 2019). Drawing on the theory of organizational decision, path dependence, etc., this paper summarizes the classification of knowledge boundary in existing literature as shown in Table 1.…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%
“…Researchers has also given some solutions for lessening the risks and improving the successful rate of the cross-border knowledge integration. For example, Kamuriwo and Baden-Fuller (2016) explained how and why knowledge integration of nonmodular products based on a strategic choice between internalizing and outsourcing core R&D and found externally focused approach can avoid risks by framing non-modular outsourcing as modular; Caridi-Zahavi et al (2016) suggested that CEOs with visionary innovation leadership can help build knowledge integration capability and drive firm innovation; Oldroyd et al (2019) addressed that codified knowledge across borders can be a vital component for project‐based work while study the antecedents and performance effects of cross-border knowledge transfer. The researcher also mentioned some other ways, such as hiring external inventors, diversified innovators’ background (Rosenkopf and Almeida, 2003), through brokers or M&A (Hargadon and Sutton, 1997; Nooteboom et al , 2007; Xi et al , 2020), crowd-sourcing (Insead and Dahlander, 2015; Hargadon and Sutton, 1997), etc.…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%